Vertical platysma myocutaneous flap reconstruction for oral defects using three different incision designs: experience with 68 cases. Issue 3 (March 2018) - Huang, L.; Gao, X.; Su, T.; Jiang, C.-H.; Jian, X.-C.
Abstract: This study evaluated the effects of three different incision designs for the vertical platysma myocutaneous flap (VPMF): apron, MacFee, and T-shaped. This flap was used for the reconstruction of intraoral defects following cancer ablation in selected patients. Sixty-eight cases of VPMF reconstruction were assessed: the apron incision was used in 28, MacFee incision in 22, and T-shaped incision in 18. With regard to postoperative outcomes, there were 26 cases of flap survival and two of partial necrosis with the apron incision; 20 of survival and two of partial necrosis with the MacFee incision; 15 of survival and three of partial necrosis with the T-shaped incision. Success rates were 92.9%, 90.9% and 83.3%, respectively, for VPMF with the apron, MacFee, and T-shaped incisions. A wound healing disturbance in the neck was seen in three cases of VPMF with the apron incision and one case with the MacFee incision. The MacFee incision had the best aesthetic effect, and the postoperative neck scar was more obvious for the T-shaped incision. It is recommended that VPMF with the MacFee or apron incision be used for the reconstruction of larger buccal mucosa and floor of the mouth defects, while VPMF with the T-shaped incision should be used for smaller intraoral defects, especially tongue defects of the lateral surface.